1962
DOI: 10.1901/jeab.1962.5-265
|View full text |Cite
|
Sign up to set email alerts
|

THE QUAIL, Coturnix coturnix, AS A LABORATORY ANIMAL

Abstract: The quail, Coturnix coturnix, is small, gentle, hardy, adaptable, easy to house, and economical to maintain. Wetherbee and Jacobs (1960) call it the "Drosophila of the avian laboratory," and yet this charming bird is virtually unknown to the psychological laboratory. Our preliminary investigations show that the pecking operant is readily conditioned and that little or no deprivation is necessary to maintain behavior with food as a reinforcer. Visual and temporal discriminations were very quickly made. Our obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

1967
1967
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 2 publications
1
15
0
Order By: Relevance
“…In our previous study on cytogenetic mapping of chicken homologs of human functional genes by FISH (Suzuki et al, 1999), we confirmed the possibility of the presence of conserved linkage homology for several chromosomal regions between the human and chicken genomes, as reported by other laboratories (Burt et al, 1995;Klein et al, 1996;Jones et al, 1997). The Japanese quail is a good experimental model animal owing to its small body size, short generation time, and inexpensive rearing requirements, compared with other domesticated avian species (Padgett and Ivey, 1959;Reese and Reese, 1962;Lansdown et al, 1970). The construction of a comparative map of chicken and Japanese quail chromosomes would contribute to the efficient use of genetic information about agricultural traits (e.g., growth, egg and meat production, and disease resistance) and biological traits characteristic of avian species (egg laying, brooding, feathering, imprinting, etc.)…”
supporting
confidence: 85%
“…In our previous study on cytogenetic mapping of chicken homologs of human functional genes by FISH (Suzuki et al, 1999), we confirmed the possibility of the presence of conserved linkage homology for several chromosomal regions between the human and chicken genomes, as reported by other laboratories (Burt et al, 1995;Klein et al, 1996;Jones et al, 1997). The Japanese quail is a good experimental model animal owing to its small body size, short generation time, and inexpensive rearing requirements, compared with other domesticated avian species (Padgett and Ivey, 1959;Reese and Reese, 1962;Lansdown et al, 1970). The construction of a comparative map of chicken and Japanese quail chromosomes would contribute to the efficient use of genetic information about agricultural traits (e.g., growth, egg and meat production, and disease resistance) and biological traits characteristic of avian species (egg laying, brooding, feathering, imprinting, etc.)…”
supporting
confidence: 85%
“…Japanese quail were first reported as a useful research model by Padgett & Ivey (1960) and since then have become a common laboratory species for a range of investigations including developmental, behavioural and environmental investigations. It is important to note that the Japanese quail should not be confused with the larger American bobwhite quail (Colinus virginianus), which is a member of the Odontophoridae family and has a longer developmental ontogeny than the Japanese quail (Reese & Reese, 1962). Although the bobwhite quail is used in some developmental studies and has been staged (Hendrickx & Hanzlik, 1965), it has a more common use in toxicity investigations.…”
Section: Introductionmentioning
confidence: 99%
“…The Japanese quail has been used for lab. studies (Padgett and Ivey, 1959;Wilson et al,1961, Reese andReese, 1962).Today work on coturnix is carried out by very few researchers across India (Woodard andWilson, 1963, Charde, 1998) as well as abroad (Vasconcelos de Moraes et al, 2008). In this context studies on eggs of Japanese quail Coturnix coturnix japonica were undertaken with respect to shell weight, embryo weight as well as yolk weight during a period of 18 days time in incubation.…”
Section: Introductionmentioning
confidence: 99%